Perempuan Tangguh, Ekonomi Tumbuh: Pemberdayaan UMKM Pempek Rumah Nenek sebagai Strategi Kesetaraan Gender pada Era Digital di Kecamatan Medan Johor - Pretty Naomi Sitompul; Fransiska Sirait; Khairani Khairani (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This community service program aims to strengthen women-led micro-enterprises through the integration of appropriate technology and digital business practices. The program was implemented at Pempek Rumah Nenek in Medan Johor using a participatory approach involving four stages: needs identification, production and packaging assistance, financial digitalization using the YouTab application, and digital marketing activation. The results show a significant improvement in production capacity and market reach. The implementation of vacuum packaging and freezing technology extended product shelf life and enabled intercity distribution. In addition, monthly revenue increased from IDR 1.5–2 million to approximately IDR 3.5 million. The program also enhanced managerial capacity and confidence among women entrepreneurs. This study demonstrates that appropriate technology combined with participatory methods can improve the competitiveness of micro-enterprises and support inclusive digital transformation.